Temperature and humidity monitoring and diagnosis system in vehicle engine by Using Internet of Things - S Sampath Kumar; A Gnan Reddy (The Bioscan, 2024)
A temperature alarm architecture will be used in order to accomplish the objective of this research, which is to construct an Internet of Things base system that is capable of detecting and monitoring overheating in automobiles. A constant beep alarm technology that can aware vehicle owners when the engine is overheating while displaying the current temperature on the vehicle dashboard is the goal of this study. The system will automatically generate information regarding the readings of vehicle temperature and send it to the storage device for future uses. Additionally, the system will design an automatic diagnostic solution on the instrument panel in the event of an emergency situation involving the engine overheating. Lastly, the system will provide a system that can make monitoring and rapid detection of vehicle engine temperature faster for individuals who are disabled or elderly or who have impaired vision. This research was motivated by a number of factors, including the absence of a vehicle blaring alarm system that would allow car owners to regulate the temperature and humidity gauge readings of their vehicle, as well as the absence of an instant diagnostic measure in the event that an emergency situation involving an overheated vehicle engine happens. The database design for the suggested system was carried out with the assistance of the Object-Oriented Analysis Design Methodology (OOADM), the Arduino Integrated Development Environment (IDE), the DHT11 humidity and temperature sensor, and the MySQL XAMPP Server. A gadget that was enabled by the Internet of Things was developed as a consequence, and it was able to detect an increase in temperature in a car by means of a beeping warning sign.